The mathar orna and authority among middle-class Bangladeshi women: Personal reflections on a collective phenomenon - Zaman, Rubaiyat (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.